Avaliação do potencial biotecnológico de compostos isolados de Swietenia macrophylla no tratamento de câncer - BARRETO, Leilane de Holanda (Universidade Federal do Pará, 2017)
Swietenia macrophylla (mahogany) is a species of plant widely known for its therapeutic potential. The main constituents isolated extracts of this plant are structures known as limonoids. The limonoids also have several biological activities, among them, antitumor activity. The aim of this study was to evaluate the antitumor potential of the extract and limonoid obtained from leaves of S. macrophylla in cancer cell lines. Cytotoxicity to 5 cancer cell lines and normal revealed that the extract had cytotoxic effect in colorectal cancer cell lines (HCT-116 and HT-29), as the limonoids were cytotoxic for colorectal cancer (HCT-116) and melanoma (SKMEL-19). Given these results, we selected the limonoid L3 and HCT-116 cell line to evaluate the mechanism of action, as well as the HT-29 lineage, which has the TP53 gene mutated for comparison as possible of the compound mechanism of action, once it was less sensitive to L3. Moreover, L3 showed more selective for tumor cells. None of the compounds caused hemolysis of erythrocytes in mice. To evaluate the antiproliferative action of L3, the clonogenic assay was performed, where the two lines there was a significant reduction of colonies, however this reduction was more significant in HCT-116. The L3 compound also has caused death by apoptosis in a dose-dependent manner in the lines, where the number of cells in apoptosis was higher in HCT-116. To evaluate DNA damage, it was held the comet assay, which showed that L3 cause damage to the DNA of the two cancer cell lines, with greater damage index in HCT-116. The assessment of cell cycle distribution of cells after treatment with L3 showed that there was blocking the cycle at the G2 / M phase, mainly in HCT-116 (45% of the cells). From these data, it conducted a study of genes involved in this phase of the cycle, from analysis of their expression by RT-PCR. The ATM gene, which is activated by DNA damage activates the CHK-2 which in turn phosphorylates p53 protein. p53 protein can activate the transcription of p21 gene, which triggers cell cycle stopped, or activate cell death pathways. In this study, we found increased expression of genes ATM, CHK-2, TP53, ARF in a dose dependent in both cacer cell lines, and this expression was higher in HCT-116 cell line. The expression of p21 was increased in HCT-116, while in HT-29 decreased, this is due to the fact that HT-29 possess the mutant TP53 gene, then your protein does not work properly. As the path of apoptosis was evaluated caspase-3 gene and the anti-apoptotic gene BCL-2. There was increase in the expression of caspase-3 mainly in HCT-116 and decrease of BCL-2. These results suggest that L3 may be causing damage to the DNA of cells, triggering a cellular signaling pathway dependent on p53. To evaluate the toxicity of S. macrophylla extract, it was held the acute toxicology testing in mice, where the extract did not cause any changes in the physiological parameters of animals. As the claustogenicidade test (micronucleus) also showed that the extract is not mutagenic in the mouse bone marrow cells.